SITUACIÓN SOCIOECONÓMICA EN FAMILIAS DISFUNCIONALES Y SU INFLUENCIA EN EL RENDIMIENTO ACADÉMICO DE LAS/LOS ESTUDIANTES DE LA ESCUELA DE EDUCACIÓN BÁSICA “JOSÉ INGENIEROS”, DE LA CIUDAD DE LOJA - Aillón Muima, Mariuxi Soledad (2019)
The present research work entitled SOCIOECONOMIC SITUATION IN DYSFUNCTIONAL FAMILIES AND THEIR INFLUENCE ON THE ACADEMIC PERFORMANCE OF THE STUDENTS OF THE BASIC EDUCATION SCHOOL "JOSÉ INGENIEROS", OF THE CITY OF LOJA, is based on a study carried out on students of 6 And 7th year of basic education, parents, teachers, director and coordinator of the DECE with the aim of contributing with a proposal of social action that allows to strengthen family communication and improve the interpersonal relationships of students. The general objective and the specific objectives that were proposed allowed to make a diagnosis of the socioeconomic situation and family dysfunction as a determining factor in the students' academic performance, identifying the effects that are manifested in the children coming from dysfunctional homes and as this influences the students' learning, the information obtained from the focus groups and the socioeconomic record was also analyzed and a social action proposal was designed that responds to the fourth specific objective of the research. The main findings were obtained through the use of methods such as the scientific, inductive, deductive, analytical, descriptive method and graffar method and the techniques used were the interview, direct observation, score sheet, socioeconomic record and focus groups applied to students, parents, teachers, psychologist and director of the basic education school "José Ingenieros", from the city of Loja. The results of the research show that the 6th and 7th grade students of basic education have low academic performance, due to factors such as poor communication, living with stepparents, distrust between parents and children, alcoholism on the part of some member of the family and separation of parents, all this has resulted in attitudes of bad behavior, aggressiveness, low self- 5 esteem, depression, queimportance, irresponsibility, insecurity, rebellion, difficulty in relationships with friends, significantly affecting academic performance. Similarly, it was found that the socioeconomic situation does not greatly influence the academic performance of students, since other factors cause low performance, such as the family environment and structure. The information that finally makes possible the design of the "SCHOOL FOR PARENTS" ON THE FAMILY AND ITS INFLUENCE ON THE ACADEMIC PERFORMANCE OF THE CHILDREN OF THE SCHOOL OF BASIC EDUCATION, OF THE CITY OF LOJA, with the implementation of workshops for Parents, participation of professionals who contribute to improving the performance of children, requiring the collaboration of authorities, parents, students and teachers.